2018
DOI: 10.1093/geront/gnx192
|View full text |Cite
|
Sign up to set email alerts
|

“I Feel Worn Out, as if I Neglected Myself”: Older Patients’ Perspectives on Post-hospital Symptoms After Acute Hospitalization

Abstract: Impairment in mobility and instrumental activities of daily living was the dominant experience for interviewed patients. This disability was mainly attributed to four main symptoms: fatigue, apathy, unsteadiness while standing, and fear of falling. We propose a tentative model that summarizes the role of posthospital symptoms in the recovery process and the potential syndromes (frailty, posthospital syndrome, palliative symptoms, and sickness behavior) that could underlie these shared symptoms which may act as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 51 publications
4
50
1
Order By: Relevance
“…Although decreasing over the postdischarge course, prevalence rates remained high postdischarge, which is consistent with previous qualitative results. 14 Taking into account findings of earlier studies that fatigue, fear of falling, 36 and apathy 37 are often present in older community dwellers, it is perhaps not surprising that these syndromes were highly prevalent in our study population. Yet, these conditions are not commonly acknowledged geriatric syndromes and have not been addressed in previous studies on geriatric syndromes in hospitalized patients.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Although decreasing over the postdischarge course, prevalence rates remained high postdischarge, which is consistent with previous qualitative results. 14 Taking into account findings of earlier studies that fatigue, fear of falling, 36 and apathy 37 are often present in older community dwellers, it is perhaps not surprising that these syndromes were highly prevalent in our study population. Yet, these conditions are not commonly acknowledged geriatric syndromes and have not been addressed in previous studies on geriatric syndromes in hospitalized patients.…”
Section: Discussionmentioning
confidence: 49%
“…19 Besides, in qualitative research apathy has been found to be highly present among older patients during the postdischarge period. 14 In the somatic domain, acknowledged geriatric syndromes such as pain, malnutrition, and incontinence were assessed. 3,4 Dizziness was included, because it is often the result of a multifactorial interplay between medical and functional aspects in older individuals, 20e22 and is associated with other geriatric syndromes such as functional decline.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Barriers to increasing physical activity in older people post-acute hospitalization include a lack of energy, health problems that they perceive as limiting movement and that few had been advised to be active so it was not important 110 . Older patients views after hospitalization report fatigue, apathy, unsteadiness while standing, and fear of falling, all perceived as effects of the hospital stay itself 111 . This highlights consistent messaging about activity and regular mobilization (through regular sit to stands and walking to help maintain levels of strength and balance) in this population are important.…”
Section: Following Hospitalizationmentioning
confidence: 99%